Differentiating the Imperial and the Colonial in Southeast Asian Literature in English: The Redundancy of Courage and The Gift of Rain - Dasenbrock, Reed Way (SARE: Southeast Asian Review of English, 2017)
There would of course be no post-colonial literature in European languages if there had been no European colonialism in the first place. Post-colonial literature stands in a close relationship- often sympathetic, though sometimes agnostic- to the literature of the European colonial power, but the point of origin for much of the literature is a relationship of antagonism- indeed, explicit opposition- to the fact of European colonial power. It is not always remembered that 'post-colonial literature' begins in the colonial period, and many of the classics of post-colonial literature date from the colonial period or were written in the imemdiate aftermath of the anti-colonial struggle.